2023
DOI: 10.1101/2023.06.21.23291661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mexican dataset of a repetitive transcranial magnetic stimulation clinical trial on cocaine use disorder patients: SUDMEX TMS

Diego Angeles-Valdez,
Jalil Rasgado-Toledo,
Viviana Villicaña
et al.

Abstract: Cocaine use disorder (CUD) is a worldwide problem with severe health and socio-economic consequences, which results in behavioral, cognitive, and neurobiological disturbances. Consensus on treatments are still under discussion, however, repetitive transcranial magnetic stimulation (rTMS) has been proposed as a promising treatment for medication-resistant disorders, including substance use disorders. Here, we describe the Mexican dataset of an rTMS clinical trial in patients with CUD (SUDMEX-TMS), a longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Data were obtained from a clinical trial conducted at the Clinical Research Division of the National Institute of Psychiatry in Mexico City, Mexico, which was approved by the Institutional Ethics Research Committee (CEI/C/070/2016), registered at ClinicalTrials.gov (NCT02986438), and acquired as part of the SUDMEX‐TMS database. 15 Detailed recruitment information, a CONSORT flowchart, and a complete demographics table, as well as the main clinical and fMRI study results, can be found in Angeles‐Valdez et al, 15 our previous publication by Garza‐Villarreal et al 16 and some details in the Supporting Information. During the clinical trial, patients with CUD who met the inclusion and did not meet exclusion criteria provided written informed consent to participate, per the Declaration Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were obtained from a clinical trial conducted at the Clinical Research Division of the National Institute of Psychiatry in Mexico City, Mexico, which was approved by the Institutional Ethics Research Committee (CEI/C/070/2016), registered at ClinicalTrials.gov (NCT02986438), and acquired as part of the SUDMEX‐TMS database. 15 Detailed recruitment information, a CONSORT flowchart, and a complete demographics table, as well as the main clinical and fMRI study results, can be found in Angeles‐Valdez et al, 15 our previous publication by Garza‐Villarreal et al 16 and some details in the Supporting Information. During the clinical trial, patients with CUD who met the inclusion and did not meet exclusion criteria provided written informed consent to participate, per the Declaration Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Field maps intended for DWI‐HARDI use were acquired using a SE‐EPI sequence with the following parameters: TR/TE = 9000/127 ms, flip angle = 90°, matrix = 128 × 128 (for four participants = 112 × 112), voxel size = 1.8 × 1.8 × 2.5 mm (for four participants = 2 × 2 × 2.3 mm), number of slices = 57 (for four participants = 58), phase encoding direction = PA. A total of seven b0 volumes were acquired. Quality control (QC) of the T1w and DWI‐HARDI images are described in the data report of SUDMEX‐TMS, 15 using EDDY_QC to extract QC metrics sensitive and specific to artefacts, besides a visual inspection before and after preprocessing step ensuring good quality and the reliability of the included data and performed analyses.…”
Section: Methodsmentioning
confidence: 99%